2018
DOI: 10.1111/bjd.15651
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine regulation of melanogenesis

Abstract: Melanocytes are generally characterized by the basic ability of melanin synthesis and transfer to adjacent keratinocytes. This constitutes an individual skin phenotype and provides epidermal protection from various stimuli, such as ultraviolet irradiation, through a complex process called melanogenesis, which can be regulated by autocrine or paracrine factors. Recent evidence has revealed the paracrine effects of keratinocytes on melanogenesis by secreting cytokines, including α-melanocyte stimulating hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 84 publications
(217 reference statements)
3
102
0
3
Order By: Relevance
“…The most well-known receptor on melanocytes that modulates their function is the melanocortin-1 receptor (Mc1r). When α-melanocyte-stimulating hormone (α-MSH) binds to Mc1-r on the membrane of melanocytes, it activates adenylate cyclase, increases intracellular caMP, activates PKa-caMP response element-binding protein (creB) pathway, and then increases MiTF, promoting melanogenesis (25)(26)(27)(28). Mc1r is also a major regulator of human pigmentation and is also a melanoma susceptibility gene (28).…”
Section: Signaling Pathways Regulating Melanogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-known receptor on melanocytes that modulates their function is the melanocortin-1 receptor (Mc1r). When α-melanocyte-stimulating hormone (α-MSH) binds to Mc1-r on the membrane of melanocytes, it activates adenylate cyclase, increases intracellular caMP, activates PKa-caMP response element-binding protein (creB) pathway, and then increases MiTF, promoting melanogenesis (25)(26)(27)(28). Mc1r is also a major regulator of human pigmentation and is also a melanoma susceptibility gene (28).…”
Section: Signaling Pathways Regulating Melanogenesismentioning
confidence: 99%
“…2). Melanocytes interact with these surrounding cells by expressing corresponding receptors on the cell surface (27). in addition, studies have revealed that paracrine factors can provide a variety of mechanisms to activate dna repair mechanisms by activating different receptors and signaling pathways to maintain melanocyte homeostasis and prevent uV mutagenesis (28).…”
Section: Signaling Pathways Regulating Melanogenesismentioning
confidence: 99%
“…In an attempt to provide greater insight into the potential mechanism of action of HSA, particularly on the potential paracrine effect of fibroblasts after treatment, on the expression of pore and age spot problems, we examined changes in secretome of fibroblasts (cell culture conditioned media), determined by mass spectrometry‐based proteomics, that might influence the fibroblasts in an autocrine fashion or keratinocytes or melanocytes in a paracrine fashion . Dermal fibroblasts play a key role in ECM formation and melanocyte pigmentation .…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of melanogenic paracrine factors can also be derived from both keratinocytes and fibroblasts as a result of UV‐induced oxidative stress . Downregulation of genes involved in epidermal differentiation has also been reported in age spots as well as decreased expression of filaggrin and involucrin .…”
Section: Introductionmentioning
confidence: 99%
“…Since induction of pigment production and secretion in MCs is a crucial protective response in 139 the epidermis that can be regulated by paracrine signaling (Serre et al, 2018;Yuan and Jin, 2018), 140 we next tested MC pigment secretion following incubation with conditioned media from KCs with 141 normal or suppressed Dsg1 expression. MCs were grown for 7 days in a 1:1 mixture of MC media 142 and media conditioned by KCs days 3-5 after initiation of differentiation.…”
Section: Exposure To Dsg1-deficient Kc Conditioned Media Increases MCmentioning
confidence: 99%